Impact of performance evaluation system on employee performance in Nigeria local government administration: A Study of Ukwuani local government administration of Delta State Nigeria - Imene, Aroghene (Journal of Social Sciences and Management Studies, 2023)
The study investigated the impact of performance evaluation system on employee performance in Nigeria Local Government Administration: A study of Ukwuani Local Government Administration (LGA) of Delta State, Nigeria. The research looked at impact of performance evaluation system such as Established Performance Standards (EPS), Communicating Performance Expectation (CPE), Measuring Actual Performance of Employee Based on Established Standards (MAPEBES), Discussion on Evaluation Result and Giving Feedback, (DERGF) and Decision Making(DM) on Employee Performance of LGA in Nigeria. The study used  survey research design to collect data from targeted respondents. A total sample size of 195 was determined using Yaro Yamane's formula. The data was analyzed using simple percentages, descriptive statistics and correlation matrix was used to determine relationship that exists between the independent and dependent variables. The hypotheses were tested using multiple regression analysis through SPSS 23. The study discovers that EPS, CPE, MAPEBES, DERGF and DM has significant and positive effect on employee performance in LGA in Nigeria. The study recommended that LGA in  Nigeria should uphold and magnify their established standards so as to bring about better employee performance. LG top managers should be able to relate how well their staff is doing on the task assign to them as this would enable them to build on their areas of weakness. Mechanism should be put in place to evaluate if actually the output of LG staff is in line with established standard and to reward accordingly. Also, the outcome of how well LG staff performed should be related to them so as to bridge noticeable gap in performance. Finally, making of decisions in this level of government should be encompassing and accommodative in order not to slow down performance of the employees.